2021
DOI: 10.1007/s00066-021-01815-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of EBRT and I-125 seed brachytherapy concerning outcome in intermediate-risk prostate cancer

Abstract: Purpose This study’s objective was the comparison of external beam radiotherapy (EBRT) and I‑125 seed brachytherapy regarding clinical outcome and development of side effects. Patients and methods In all, 462 localized intermediate-risk prostate cancer patients treated between 2000 and 2019 at our department using either I‑125 seed brachytherapy or EBRT with a dose of 74 or 78 Gy were included: 297 patients were treated with EBRT and 165 with seeds. Bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This effect is commonly exploited in various modalities, has been long known and accounted for in the clinic heuristically, and can be advantageous for sparing of adjacent normal tissue. 2,9,53 Indeed, the source we used in this set of experiments, I125, is classified as a low-dose rate (LDR) BT, requiring in our chip roughly 2 hours to deliver the 8 Gy target to the first row of spheroids. 7,9 By contrast, EBRT delivered using the GammaCell cabinet treated spheroids with 8 Gy in around 2 minutes, a 60-times higher dose rate.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is commonly exploited in various modalities, has been long known and accounted for in the clinic heuristically, and can be advantageous for sparing of adjacent normal tissue. 2,9,53 Indeed, the source we used in this set of experiments, I125, is classified as a low-dose rate (LDR) BT, requiring in our chip roughly 2 hours to deliver the 8 Gy target to the first row of spheroids. 7,9 By contrast, EBRT delivered using the GammaCell cabinet treated spheroids with 8 Gy in around 2 minutes, a 60-times higher dose rate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported a 15 years disease-free survival rate of 80.4% after treatment of men with localized prostate cancer with BT [ 57 , 58 ]. Another studies reported a 5 years and 10 years OS rate of 94% and 84%, respectively, among similar patients [ 59 ].…”
Section: Discussionmentioning
confidence: 99%